2020
DOI: 10.1101/2020.03.07.982108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic-induced disturbances of the gut microbiota result in accelerated breast tumour growth via a mast cell-dependent pathway

Abstract: One Sentence Summary:We show that breast cancer progression is accelerated through a unique/novel immune response involving mast cells as a result of an antibiotic induced perturbation of the gut microbiota in a mouse model. AbstractThe diverse community of commensal microbes that comprise the gut microbiota is known to play an integral role in human health, not least through its ability to regulate host immune responses and metabolic pathways. Alterations to the homeostasis of this community, including throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Previously we showed that bacterial tryptophan metabolism is suppressed in early stages of breast cancer, releasing the brake on breast cancer cells [ 16 , 17 , 40 ]. In that sense, IS behaves similar to other cytostatic metabolites [ 16 , 17 , 25 , 32 , 39 , 40 , 41 , 42 , 43 , 45 , 46 ]. Of note, in addition to the loss of cytostatic properties, the breast cancer oncobiome has an increased capacity for reactive estrogens and increase estrogen enterohepatic circulation [ 1 , 93 ].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previously we showed that bacterial tryptophan metabolism is suppressed in early stages of breast cancer, releasing the brake on breast cancer cells [ 16 , 17 , 40 ]. In that sense, IS behaves similar to other cytostatic metabolites [ 16 , 17 , 25 , 32 , 39 , 40 , 41 , 42 , 43 , 45 , 46 ]. Of note, in addition to the loss of cytostatic properties, the breast cancer oncobiome has an increased capacity for reactive estrogens and increase estrogen enterohepatic circulation [ 1 , 93 ].…”
Section: Discussionmentioning
confidence: 87%
“…Lower biosynthetic capacity is associated with ER cases [ 40 , 51 ] or triple negative cases [ 9 , 12 , 13 ] that have worse clinical outcomes. In addition, the application of antibiotics, which suppress microbial diversity, increases the risk for breast cancer in human and animal studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 82 ]. On the other hand, probiotic treatment, which enriches the gut microbiome, decreases the incidence of breast cancer [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical or systemic antibiotic treatment has a strong impact on the composition of the microbiome. Antibiotic treatment impacts the frequency and recurrence of breast cancer (Friedman et al 2006 ; Kirkup et al 2019 , 2020 ; Wirtz et al 2013 ). In the case of pancreatic adenocarcinoma where bacterial colonization of the pancreas is a major driver of carcinogenesis (Kiss et al 2020 ) similar to ovarian cancer, antibiotic treatment was beneficial in animal models (Thomas et al 2018 ).…”
Section: Modulating the Oncobiome In Ovarian Cancermentioning
confidence: 99%